Review: Pengaruh Efektivitas Ekstrak Kopi Arabika Sebagai Antioksidan Dan Bentuk Sediaan Farmakologi - Rahasbistara, Made Rendra Wisnu; Melani, Ni Ketut Lyra Sakhya (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Indonesia is a country abundant in natural resources. Indonesia is home to a large number of Arabica coffee plants (Coffea arabica L.) which are now highly valued internationally. This plant is known to have various biological effectiveness, especially due to the antioxidant content of Arabica coffee extract. Based on reviews, Arabica coffee extract has significant antioxidant capacity, containing bioactive compounds such as chlorogenic acid and caffeine. In society, Arabica coffee is generally used as herbal medicine and drinks with standard processing. However, current research and reviews continue to develop various formulations and innovations from Arabica coffee to increase its therapeutic benefits. Several pharmacological dosage forms such as capsules, tablets, creams, and serums have been successfully developed to maximize the therapeutic benefits of Arabica coffee extract. This article will discuss comprehensively the chemical content, biological activity, and various innovative formulations that have been developed from Arabica coffee. All of this shows that Arabica coffee has great potential to be further developed as an effective active ingredient in various therapeutic applications, making a significant contribution to the fields of health and medicine.